2017
DOI: 10.1177/0018720816684064
|View full text |Cite
|
Sign up to set email alerts
|

Is Domain Highlighting Actually Helpful in Identifying Phishing Web Pages?

Abstract: Potential applications include development of phishing prevention training incorporating domain highlighting with other methods to help users identify phishing Web pages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
(44 reference statements)
1
34
0
Order By: Relevance
“…So, domain name highlighting cannot be used as a single method for detecting phishing webpages. A similar study has been done on a larger scale (320 participants), which resulted in a similar conclusion [213].…”
Section: Selected User Study Literaturesupporting
confidence: 59%
See 1 more Smart Citation
“…So, domain name highlighting cannot be used as a single method for detecting phishing webpages. A similar study has been done on a larger scale (320 participants), which resulted in a similar conclusion [213].…”
Section: Selected User Study Literaturesupporting
confidence: 59%
“…[266] 4 [225], [229], [247], [265] 2 [233], [252] 1 [219] No 6 [10], [230], [238], [249], [250], [258] 3 [242], [260], [263] Webpage Yes 5 [204], [239], [245], [253], [261] No 4 [203], [212], [236], [264] 3 [211], [213], [216] 3 [61], [217], [ [232] in [211] and [214] used Functional Magnetic Resonance Imaging (fMRI) and Electroencephalogram (EEG) to measure brain's electrical activity and an eye-tracker to have a better understanding of users' decision-making process. They used both existing phishing websites (by downloading and hosting them on their own network) and manually created ones.…”
Section: Selected User Study Literaturementioning
confidence: 99%
“…Human education papers commonly teach users how to parse out the domain as a way of enabling them to compare the domain to the one they expect to be visiting [12,36]- [38]. However, people struggle to retain these skills [36].…”
Section: A Url Lexical Featuresmentioning
confidence: 99%
“…Human-facing methods in our dataset did not consider the URL length as a feature; nevertheless, participants in [38] assumed the longer the URL the less secure it was. Alsharnouby et al [26] also found that people without training tend to classify URLs based on their perceived simplicity.…”
Section: A Url Lexical Featuresmentioning
confidence: 99%
“…For example, incorporating fear appeals into a password strength meter has been shown to be effective in pushing users towards creating stronger passwords in a field experiment setting (Vance et al 2013). Also, interactively highlighting potentially risky domain names has been shown to be effective in preventing users from visiting phishing websites (Xiong et al 2017). Evidently, this form of assistance is incredibly useful in shaping user behavior and thus has been a focus for both academic researchers and practitioners in the area of information security in recent years.…”
Section: Active Interventionmentioning
confidence: 99%